Employment Consequences of Employment Protection Legislation - Per Skedinger (Research Institute of Industrial Economics (IFN), 2011)
This article surveys the literature and adds to the evidence on the impact of employment protection legislation on employment. While stringent employment protection contributes to less turnover and job reallocation, the effects on aggregate employment and unemployment over the business cycle are more uncertain. Exploitation of partial reforms and the use of micro data in recent research appear not to have affected results regarding employment and unemployment in any systematic way. Labour market prospects of young people and other marginal groups seem to worsen as a consequence of increased stringency of the legislation. It is debatable whether marginal groups have gained much from the widespread policy strategy to liberalize regulations of temporary employment and leave regulations of regular employment intact. My own analysis suggests that increased stringency of regulations for regular work is associated with a higher incidence of involuntary temporary employment, particularly among the young.
Keywords: J23; J50; K31; 330; Job security; Employment effects; Employment protection reforms; Arbeitnehmerschutz; Kündigungsschutz; Beschäftigungseffekt; Junge Arbeitskräfte; Europa